Students Personal Learning Effort and Effective Learning Environment in Academic Performance - Shrestha, Chandra Maya; Ale, Jenisha (DAV Research Journal, 2025)
This study examines the impact between student’s personal learning efforts and institutional support systems in shaping academic performance. It aims to identify how self-regulated learning strategies interact with environmental factors to influence educational outcomes. A quantitative cross-sectional design was employed, and 229 final responses was used from undergraduate levels students. Data were collected using five point Likert-scale questionnaires. Correlation and regression analyses were conducted using SPSS version 20. Results revealed that proactive learning behaviors (goal-setting and time management) and supportive environments (structured curricula and faculty engagement) jointly enhance academic performance whereas motivation showed the strongest predictive power and library access had negligible impact without training. This concludes that academic success requires simultaneous development of student agency and institutional capacity. Findings advocate for integrating self-regulation training into curricula, faculty development programs for student-centered teaching and policy reforms addressing digital research literacy gaps. Institutions could balance resource provision with skill-building initiatives.